Theoretic insights on the concept of internal fit of HR elements within the construct of high performance work system - Khurram Rehmani (Production and Manufacturing Research: An Open Access Journal, 2021)
The ‘system perspective’ concept has intensely been supported by strategic human resource management researchers , who have so far been fairly successful in producing substantial evidence to prove that synergistic and mutually reinforcing human resource (HR) practices bonded together in ‘bundles’ , can significantly affect the performance of organizations at multiple-levels . To understand how HR activities interrelate to generate positive (negative) synergistic effects and affect performance across multiple levels, it is necessary to comprehend the pattern of relationships within HR activities.  However, limited efforts have been made to explore the nature of the ‘Internal-Fit’of HR elements within the construct of HPWS. This research study aims (1) to develop a multi-leveltheoretical framework of HPWS to illustrate how aligned and interrelated HR activities can generate synergistic effects that may affect performance at multiple levels and (2) to clarify the nature of ‘Internal-Fit’ of HR elements in both horizontal and vertical dimensions within HPWS.